2022
DOI: 10.3389/fpubh.2022.963760
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smoking (cigarette and waterpipe) and its association with obesity/overweight in UAE and Palestine

Abstract: AimThis study aimed to assess the prevalence rate of smoking behavior (cigarette and waterpipe) and its association with obesity/ overweight among university students in the United Arab Emirates (UAE) and Palestine.MethodsA cross-sectional study was conducted at a convenient sample of 10 largest universities in the West Bank- Palestine and Dubai- UAE. In total, 3800 students were randomly selected from the universities, with an 87.6% response rate. A self-administered questionnaire was used to collect the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In addition, a follow-up study in four Arab countries, including the UAE, indicated that several unfavorable lifestyle and dietary habits persisted even after the availability of the COVID-19 vaccine, indicating that people might have continued with eating habits acquired during the COVID-19 lockdown [ 71 ]. One recent study found that smoking was significantly associated with high BMI in university students in both Dubai and Palestine [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a follow-up study in four Arab countries, including the UAE, indicated that several unfavorable lifestyle and dietary habits persisted even after the availability of the COVID-19 vaccine, indicating that people might have continued with eating habits acquired during the COVID-19 lockdown [ 71 ]. One recent study found that smoking was significantly associated with high BMI in university students in both Dubai and Palestine [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the prevalence of obesity and overweight was higher among females in the UAE, which could be explained by the fact that women have more cultural constraints in their lifestyles and physical activities than men [ 115 ]. Smoking and physical activity were associated with BMI in the UAE, as the smoking of waterpipes was associated with increased waist circumference and increased BMI [ 72 ]. Moreover, TV viewing and reduced physical inactivity were associated with increased BMI among adults in the UAE [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the 2015 Youth Survey show that 23.5% of Palestinians aged 15–29 use cigarettes, with male respondents using tobacco at a higher rate (40.9%) than female respondents (5.4%) 7. Of university students, approximately 30% were identified as current tobacco users, 22.0%–25.0% as current waterpipe smokers and 18.0% as current cigarette smokers, with male students significantly more likely than female students to use cigarettes 10–12…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, hookah smoking is usually associated with long-term sitting in cafes, which leads to inactivity and increased food consumption and obesity. 16 Obesity makes people susceptible to noncommunicable diseases such as diabetes and metabolic syndrome. 17 Metabolic syndrome is associated with various symptoms such as increased abdominal obesity, increased blood pressure, decreased high-density lipoprotein (HDL) cholesterol, increased serum triglycerides, and increased glucose concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Hookah smoke contains higher levels of carbon monoxide (CO) and polyaromatic hydrocarbons than cigarettes, which enter the body and accumulate there 14 and led to different cancers 15 . In addition, hookah smoking is usually associated with long‐term sitting in cafes, which leads to inactivity and increased food consumption and obesity 16 . Obesity makes people susceptible to noncommunicable diseases such as diabetes and metabolic syndrome 17 …”
Section: Introductionmentioning
confidence: 99%